Cross-border Mergers and Acquisitions and ShareholderWealth: A China-U.K. Comparison - Lin, Guozhen (2015)
Abstract: Cross-border mergers and acquisitions (CBM&As), as a mode of foreign direct investment (FDI) are becoming increasing popular in both developed and emerging economics. This paper aims to fill the gap of lack of comparative studies on CBM&As between developed-country firms and developing-country firms. This paper investigates the performance of acquiring firms from China and the U.K. Using event study, CBM&As create value for shareholders of acquiring firms from both countries.. Financial crisis is considered to be an opportunity for Chinese acquiring firm expands internationally. Performances of transactions made by Chinese acquiring firms in crisis years have a higher abnormal return compare to transactions made in other years. In contrast, crisis year acquisitions by U.K acquirers earn a lower return compare to transactions in others years. Furthermore, high-tech acquisitions by Chinese acquiring firms have a better performance than the U.K. acquiring firm.